If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(6x+3)+2(x-1)=109
We move all terms to the left:
5(6x+3)+2(x-1)-(109)=0
We multiply parentheses
30x+2x+15-2-109=0
We add all the numbers together, and all the variables
32x-96=0
We move all terms containing x to the left, all other terms to the right
32x=96
x=96/32
x=3
| |3y-2|=10 | | 8.2+t/2=1.7 | | -2|-2x+1|+3=7 | | -9=v/13 | | 2k-5=3(1-2k | | -2|-2x+1|+3=7 | | 4(−4x+2)+2x+5=−57 | | 15+2-4=9x+11-7x | | 3+4.x=17-3.x | | 4x+2=2x+8-2 | | 5n+25=2n+22 | | 0.9*x+6=51 | | 6x-1+7x-1=180 | | 4-2x+x=-3-3(2-x) | | 1x+0.5x=0 | | (4u-12)-(1u+12)=18 | | 17x+6=9x | | (4u-12)-(1u+12)=0 | | 7(x-2)+1=15-7x | | m=1/2(-2,3) | | (3x-2)7=5x=14 | | 11=4z-1 | | 2x-4=8x-10 | | 4x^2-16x+16=48 | | s÷5=2 | | x/2=(x+6)/8 | | |5x−1|=|8x−1| | | 21=28-7x | | 4x+9+6x+21=180 | | x/2=(x+6)/2 | | 3x-26=2x-9 | | 0=12+3(m-5) |